DeCACHe: Supporting Designers in Creating Cognition-Centered Adaptive Cultural Heritage Activities - Raptis, George E.; Sintoris, Christos; Avouris, Nikolaos (Heritage, 2019)
Cultural heritage (CH) institutions attract wide and heterogeneous audiences, which should be efficiently supported and have access to meaningful CH content. This introduces numerous challenges when delivering such experiences, given that people have different cognitive characteristics which influence the way we process information, experience, behave, and acquire knowledge. Our recent studies provide evidence that human cognition should be considered as a personalization factor within CH contexts, and thus we developed a framework that delivers cognition-centered personalized CH activities. The efficiency and the efficacy of the framework have been successfully assessed through two user studies, but non-technical professionals (e.g., CH designers) may face difficulties when attempting to use it and create personalized CH activities. In this paper, we present DeCACHe, which supports CH designers in creating cognition-centered personalized CH activities throughout different phases of the design lifecycle. We also report a user study with seventeen professional CH designers, who used our tool to design CH activities for people with different cognitive characteristics.